Uma introdução à homologia de interseção simplicial - Souza, Thiago de Paiva (2019)
In this dissertation we study the simplicial intersection homology as introduced by M. Goresky e R. MacPherson in 1978 in the article [3]. The main result of this dissertation is the demonstration of the generalized Poincaré duality theorem of the intersection homology theory for pseudomanifolds